Characteristics of niosomes prepared by supercritical carbon dioxide (scCO2) fluid - Aranya Manosroi (2018)
Characteristics of niosomes prepared by a novel supercritical carbon dioxide fluid (scCO2) technique have been investigated. Niosomes were composed of Tween61/cholesterol at 1:0, 3:1, 1:1, 1:3 and 0:1 molar ratios and entrapped with d-(+)-glucose by the scCO2method without and with ethanol at 5, 10 and 15 % (w/w) as a co-solvent, and the conventional chloroform film method with sonication. Tween61/cholesterol at 1:1 molar ratio niosomes prepared by all methods exhibited the best physical stability. Niosomes by the scCO2method with 10 % (w/w) ethanol gave higher trapping efficiency (12.22 ± 0.26%) than those by the conventional chloroform film method with sonication (10.85 ± 0.24%) and the scCO2method without ethanol (8.40 ± 1.60%). Niosomes by the scCO2method with and without ethanol were large unilamellar structure under TEM with the average sizes of 271.9 ± 159.6 and 202.5 ± 136.7 nm, respectively, whereas those by the conventional chloroform film method with sonication were multilamellar and unilamellar structure with the average size of 58.4 ± 74.6 nm. However, the dispersibility of niosomes by the conventional chloroform film method with sonication was better than that by the scCO2either with or without ethanol, because of smaller particle size. This present study has demonstrated the trapping efficiency enhancement of water-soluble compounds in niosomes by the scCO2method with 10 % (w/w) of ethanol. © 2007 Elsevier B.V. All rights reserved.